Influence of pre-screening on down-stream processing for the production of plastic enriched fractions for recycling from mixed commercial and municipal waste. (1st January 2021) - Möllnitz, S.; Küppers, B.; Curtis, A.; Khodier, K.; Sarc, R.
Highlights: Influence of pre-screening on down-stream processing is investigated. Pre-screening improves the quality of the output. Drum sieving cleans the surface of objects and hence increases sorting yields. Selective size reduction enhances the enrichment of valuable materials. Proper pre-treatment can raise the sorting yield by 3–5%. Abstract: The use of plastic waste as resource gains more and more attention. In this context, material recycling is especially focused on packaging plastics. Further waste streams that contain a significant amount of plastics are mixed commercial and municipal solid waste. To assess the potential of plastics for recycling and energy recovery from these material streams large-scale experiments were conducted. The potential of mechanical pre-processing with the aim of generating a 3D-plastics pre-concentrate was assessed. The focus of these investigations was put on the relevance of the screening stage and its influence on down-stream material processing via ballistic separation and sensor-based sorting. Results demonstrate not only that the screening of both waste streams leads to enrichment of plastics in coarse particle size ranges (especially >80 mm) and transfer of contaminants, organics and minerals to fine fractions (especially <10 mm), but also that sensor-based sorting performance can be significantly enhanced due to cleaning effects on plastics, induced by the material circulation and the resulting interparticle friction in a drum screen. On the downside, the material rotation in a drum screen leads to tail-formation that can create plant down-time through clogging as well as material losses and impairment of pre-concentrates.